Information technologies and mathematical modelling : queueing theory and applications : 16th International Conference, ITMM 2017, named after A.F. Terpugov, Kazan, Russia, September 29-October 3, 2017, Proceedings /: queueing theory and applications : 16th International Conference, ITMM 2017, named after A.F. Terpugov, Kazan, Russia, September 29-October 3, 2017, Proceedings. (2017) - Unknown
No abstract available